Profile of Protein Levels Some Tobacco Varieties (Nicotiana tabacum L.) On Waterlogging Stress - Nurhidayati, Tutik; Novitasari, Novitasari; Purnobasuki, Herry; Hariyanto, Sucipto; Jadid, Nurul (Proceedings of the International Conference on Green Technology, 2017)
Tobacco is a high-value crops that are sensitive to waterlogging stress. Some tobacco varieties have been widely cultivated in Indonesia, including Jepon Mawar, Jepon Banyak and Rejeb. Some species have different abilities to withstand the conditions of waterlogging stress by morphological adaptation, anatomy, physiology, and metabolic pathway changes. Changes in protein profiles is one form of plant defense response to waterlogging stress. Profile proteins experienced upregulation in hypoxia and anoxia conditions when gripped waterlogging stress known as anaerobic polypeptides. In addition to the waterlogging stress will cause the decrease in chlorophyll levels as a result of chlorosis during the stress. The purpose of this research is to know protein profile and chlorophyll content of several varieties of tobacco (Nicotiana tabacum L.): Rejeb, Jepon Mawar and Jepon Many against stagnant waterlogging stress. The protein profile was analyzed by SDS-PAGE method. While the chlorophyll content was analyzed by spectrophotometric method. The protein profiles expressed from the three test varieties were present in the molecular weight range 85.38-153.33 kDa. Proteins with a molecular weight of 85.38 kDa are thought to have similarities to the Peroxsidase group (BM = 85 kDa) that play a role in the ROS detoxification process. While the chlorophyll content in the three varieties decreased with the increasing of waterlogging stress except on Rejeb varieties treated by 175% and Jepon Mawar varieties on 200% waterlogging stress treatment.